Tailored Tamoxifen Treatment for Breast Cancer Patients: A Perspective - Jager, Nynke G. L.; Linn, Sabine C.; Schellens, Jan H. M.; Beijnen, Jos H. (Elsevier, 2015)
Tamoxifen, an endocrine agent, is widely used in the treatment of estrogen receptor-positive breast cancer. It has greatly reduced disease recurrence and mortality rates of breast cancer patients, however, not all patients benefit from tamoxifen treatment because in approximately 25% to 30% of the patients the disease recurs. Many researchers have sought to find factors associated with endocrine treatment outcome in the past years, however, this quest has not been finished. In this article, we focus on a factor that might influence outcome of tamoxifen treatment: interpatient variability in tamoxifen pharmacokinetics. In recent years it has become clear that tamoxifen undergoes extensive metabolism and that some of the formed metabolites are much more pharmacologically active than tamoxifen itself. Despite the wide interpatient variability in tamoxifen pharmacokinetics and pharmacodynamics, all patients receive a standard dose of 20 mg tamoxifen per day. Different approaches can be pursued to individualize tamoxifen dosing: genotyping, phenotyping, and therapeutic drug monitoring. Therapeutic drug monitoring seems to be the most direct and promising approach, however, further clinical research is warranted to establish the added value of individual dosing in tamoxifen treatment optimization. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Endoxifen; Estrogen receptor-positive breast cancer; Metabolite levels; Therapeutic Drug Monitoring; Treatment individualization; CYP2D6 GENOTYPE; ADJUVANT TAMOXIFEN; ESTROGEN-RECEPTOR; ACTIVE METABOLITE; GENETIC POLYMORPHISMS; POSTMENOPAUSAL WOMEN; ENDOXIFEN LEVELS; THERAPY; ASSOCIATION; RECURRENCE; Taverne